Code Mixing Performed by Nessie Judge as Content Creator - Shalasah Talistah (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
YouTube content becomes an essential for the content creator. Most of content creator tends to combine two languages in their utterances which is mixing languages phenomenon on YouTube. The purposes of the research are trying to figure out the functions and reasons for mixing languages in Nessie Judge’s utterances as well as categorizing in code mixing from her YouTube videos channel. This research applies theories from Marasigan (1983) and Hoffmann (1991) in analyzing the data. This research uses descriptive qualitative method. In gaining the data analysis, there are three steps: (1) process of identifying and reducing data that have code mixing, (2) process of analyzing the data, (3) the process of verifying the analysis. The results show that there are 6 functions and 7 reasons of code mixing in this research. There are also found 4 forms of function and reason that are used by Nessie Judge namely the insertion of word, phrase, clause, and hybrid. The functions are as follows: the facility of expression, personalization and objectivization, repetition, interjection, message qualification, and addressee specification. Moreover, the reasons are used for talking about the particular topic, being emphatic about something, repetition of clarification, lexical need, expressing group identity, interjection, and the intention of clarifying the speech content for the interlocutor. Keywords: code mixing, YouTube content, content creator.